1982
DOI: 10.1097/00000658-198202000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatitis Following Parathyroid Surgery

Abstract: While pancreatitis may provide the clue to the diagnosis of hyperparathyroidism preoperatively, the occurrence of pancreatitis following parathyroidectomy is not generally recognized. In this study preoperative and postoperative serum amylase estimations, together with a clinical assessment, were performed on 86 patients undergoing neck exploration for hyperparathyroidism. It was found that postoperative hyperamylasaemia occurred in 35% of the total group, while clinically significant pancreatitis was found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

1986
1986
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 23 publications
0
14
0
1
Order By: Relevance
“…In 1962 Mixter et al reported 62 cases of pancreatitis occurring in association with primary hyperparathyroidism (PHPT) after reviewing the published work 2 . Subsequent reports have focused on the development of pancreatitis in patients who are operated on for hyperparathyroidism 3–5 . The contradictory point was raised in 1980 when Bess et al reviewed 1153 patients and showed the coexistence or history of pancreatitis in only 1.5% of patients and suggested that the association may be casual rather than causal 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In 1962 Mixter et al reported 62 cases of pancreatitis occurring in association with primary hyperparathyroidism (PHPT) after reviewing the published work 2 . Subsequent reports have focused on the development of pancreatitis in patients who are operated on for hyperparathyroidism 3–5 . The contradictory point was raised in 1980 when Bess et al reviewed 1153 patients and showed the coexistence or history of pancreatitis in only 1.5% of patients and suggested that the association may be casual rather than causal 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In this series a 3.2% incidence (40 patients) of pancreatitis was found (acute/subacute in 26 and chronic in 14). Only serum calcium level was significantly increased in HPT patients with pancreatitis when compared with those without pancreatitis.…”
Section: Discussionmentioning
confidence: 55%
“…In a series of 86 patients undergoing neck exploration for HPT reported by Reeve et al [14], the incidence of postoperative pancreatitis was 9%. A possible mechanism proposed by Lambert et al [15] to explain the onset of pancreatitis after parathyroidectomy is based on acutely elevated serum calcium level.…”
Section: Discussionmentioning
confidence: 95%
“…[42] Subsequent reports have focused on the development of pancreatitis in patients who are operated on for hyperparathyroidism. [434445] However, while some studies have found an increased incidence of pancreatitis in patients with PHPT, others have not. [37] One possible reason for this turn could be the changing profile of PHPT in the developed countries, where symptomatic disease remains uncommon and pancreatic disease with PHPT extremely rare.…”
Section: Hypercalcemiamentioning
confidence: 99%